On the E-infinity Algebras (European Journal of Pure and Applied Mathematics, 2021)
In this paper we study an elementary use of E-infinity modules and E-infinity algebras as together they have a use in terms of describing triangulated categories. Also, we show an interpretation of E-infinity algebras where the modules are fibrant objects within the categories of differential graded co-algebras and co-modules.
Keywords: Coalgebra; DG-algebras; E-innity algebra; Modules